Effect of Return On Assets (ROA), Debt To Equity Ratio (DER), Current Ratio (CR) & Stock Return on Actual Growth Rate Deviation from Sustainable Growth Rate in Infrastructure Companies on the Indonesia Stock Exchange - Mohammad Zulman Hakim; Fadila Arum Puspandari; Ahmad Jahyani; Eko Sudarmanto; Ahmad Zaki; Samino Hendrianto (Cita konsultindo, 2023)
All companies want big profits. This should increase sales growth. However, growth is not always profitable. Growing too fast can put a huge strain on a company's resources. If growth is too slow, the company is considered not to realize the company's existing financial potential. Therefore, the concept of Sustainable Growth Rate can be measured in such a way that the maximum level of sales can be increased without the company running out of financial resources. This study aims to empirically test the effect of ROA, DER, CR and Stock Return on the Deviation of Actual Growth Rate. This study used multiple regression analysis on 68 samples. companies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2021. The results show that several determinants such as DER have a positive effect on the Actual Growth Rate Deviation from the Sustainable Growth Rate. Other factors such as ROA, CR and Stock Return have a negative effect on the deviation of the actual growth rate from the sustainable growth rate